Characterizing the role of atrial natriuretic peptide signaling in the development of embryonic ventricular conduction system - Arun Govindapillai (Nature Portfolio, 2018)
Abstract Patients born with congenital heart defects frequently encounter arrhythmias due to defects in the ventricular conduction system (VCS) development. Although recent studies identified transcriptional networks essential for the heart development, there is scant information on the mechanisms regulating VCS development. Based on the association of atrial natriuretic peptide (ANP) expression with VCS forming regions, it was reasoned that ANP could play a critical role in differentiation of cardiac progenitor cells (CPCs) and cardiomyocytes (CMs) toward a VCS cell lineage. The present study showed that treatment of embryonic ventricular cells with ANP or cell permeable 8-Br-cGMP can induce gene expression of important VCS markers such as hyperpolarization-activated cyclic nucleotide-gated channel-4 (HCN4) and connexin 40 (Cx40). Inhibition of protein kinase G (PKG) via Rp-8-pCPT-cGMPS further confirmed the role of ANP/NPRA/cGMP/PKG pathway in the regulation of HCN4 and Cx40 gene expression. Additional experiments indicated that ANP may regulate VCS marker gene expression by modulating levels of miRNAs that are known to control the stability of transcripts encoding HCN4 and Cx40. Genetic ablation of NPRA revealed significant decreases in VCS marker gene expression and defects in Purkinje fiber arborisation. These results provide mechanistic insights into the role of ANP/NPRA signaling in VCS formation.